PELAKSANAAN PENERBITAN IZIN MENDIRIKAN BANGUNAN (IMB) DI ERA OTONOMI DAERAH PADA PEMBANGUNAN PERUMAHAN DI KABUPATEN SLEMAN - , Basiswan. M, SH; , Andi Sandi A.T.T., S.H., L.L.M. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Building License is a license granted by the Government to the owner of the building for a new build, modify, extend, reduce, and/or maintenance of the building in accordance with the requirements of the administrative and technical requirements. Regional Regulation Number 5 of 2011 Regarding Building is the basic implementation of the building license of residential development in Sleman Regency. This study used a normative legal approach, because it was intended to provide a detailed description of the object to be studied by using constitutional legal norms that exist and how the implementation of the building license residential development in Sleman Regency. Implementation of Building License in the era of regional autonomy on residential development in Sleman Regency is still not maximal yet. This is because the procedure is too long, a lot of terms poorly understood by the applicant that are difficult to fulfill, the cost and time in taking care of building license is ineffective and inefficient. In addition, due to the performance of the apparatus is not accountable and responsive. Obstacles encountered in the implementation building license issuance in Sleman Regency are the poor regulations, non optimal service pattern, such as the capacity of building license personnel who provide services, unsupportive facilities and infrastructure, and the inconsistent application of legal sanctions, and lack of socialization on the building license resulting in low public awareness, particularly housing developers who maintain the housing license. Efforts taken to achieve good governance in the implementation of building license issuance in the era of regional otonomy are optimizing the prime resources to maximize the achievement of excellent performance in the housing license service issuance through human resource development, improving interagency coordination through communication and information systems to improve socialization, monitoring, supervision and sanctions, as well as building surveying.